Integrating Research and Practice: Distractions, Controversies, and Options for Moving Forward. (July 2015) - Gambrill, Eileen
Integrating practice and research is vital in all helping professions in order to offer the most ethical, evidence-informed interventions to clients. This article describes some avoidable distractions that hinder integration, discusses controversies related to integration, and describes options for moving forward, including making wasted resources visible, use of an Environmental Deprivation Scale, and courage training.